2020
DOI: 10.1155/2020/5849323
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Human Esophageal Cancer Using Tandem Mass Tag Quantifications

Abstract: Esophageal cancer (EC) is a type of extremely aggressive gastrointestinal cancer with high incidences in China and other Asian countries. EC does not have specific symptoms and is relatively easy to metastasize, which makes it difficult in early diagnosis. Thus, novel noninvasive diagnostic method is urgently needed in clinical practice. In this study, mass spectrometry with tandem mass tags and differential protein analysis were applied for identifying esophageal cancer-related proteins. The identified protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…TMTs, in addition to protein quantification, increase the detection sensitivity of certain highly hydrophilic analytes, such as phosphopeptides [ 207 , 208 ]. TMTs are widely applied in oncoproteomics analysis [ 205 , 209 , 210 , 211 , 212 , 213 ].…”
Section: Advances In Proteomic Technologies Used In the Study Of Cancermentioning
confidence: 99%
“…TMTs, in addition to protein quantification, increase the detection sensitivity of certain highly hydrophilic analytes, such as phosphopeptides [ 207 , 208 ]. TMTs are widely applied in oncoproteomics analysis [ 205 , 209 , 210 , 211 , 212 , 213 ].…”
Section: Advances In Proteomic Technologies Used In the Study Of Cancermentioning
confidence: 99%
“…Esophageal cancer (ESCA) is an aggressive malignancy with poor therapeutic outcomes [ 1 ]. Alterations in proteins and posttranslational modifications (PTMs) leading to the pathogenesis of ESCA have attracted much research attention [ 2 , 3 ]. Since large-scale genome profiling has identified several driver mutations and key regulation pathways but effective targeted therapy is still lacking, discovering novel pathological alterations in proteins may give rise to advances in drug development to fulfill the gap in current drug targets.…”
Section: Introductionmentioning
confidence: 99%
“…As part of the effort to subcategorize gastroesophageal and identify biomarkers for response to treatment, previous esopahgeal cancer proteomics studies have identified markers for adverse outcome, such as GLUT1‐sialyl‐Tn antigen which is also expressed in other gastrointestinal cancers, 11 as well as differentially enriched proteins related to mitochondrial apoptosis, and regulation of angiogenesis. 12 However, most of these studies have compared esophageal cancer cells with healthy esophageal tissue cells. In the current study, we aimed to find proteomic biomarkers to predict a favorable response to neoadjuvant chemoradiation.…”
Section: Introductionmentioning
confidence: 99%